Micaretas ou festas micaretescas? sobre espaços públicos e privados, lugares e locais na turistificação da folia em Goiânia - XAVIER, Clarissa Valadares (2010)
Carnival in Brazil happens in many scenarios, but two of them are the most important related to tourism parties and festivals held there: Salvador and Rio de Janeiro. The city of Salvador, as well as other cities in Brazil, had its parties inspired those ones there were in Rio de Janeiro until the trio elétrico launched. Throughout his, it created a new way to dance which is called "chase the trio . As a walking stage, the trio has reshaped the Carnival in Salvador, and this influenced the interest of this study which aims to investigate the micaretas and parties micarestescas , which came from the electric trios from this city originally. These festivals across places around the country and brought down borders. Is permeated by a complex process of changes since its appearance in Brazil is changing of cultural dynamics. Previously regarded as festivities "off season", which was a break in the liturgical calendar, became party with their own places, with time frames that cut out the calendar. They have a loyal and appreciative audience participation as defined by a certain model of party, which is exported. Besides that, public and private management are intentionally "confused" because many of the parties left the public site of streets and placed themselves in private areas like racecourse, clubs, event spaces, etc.. It is the same case of the holiday which happens in the city of Goiania, an event that is already included in the city's calendar and happens through many paths, redefines the geography of the party, where they hide and show, or put several implicit and explicit conflicts. The relationship between tourism, geography and the parties becomes crucial in this case, for tourism, even though in this city regarding to the party which makes changes to become it so festive and to happen in a specific place for them.